The Democracy Dividend: ˗How Early Exposure to Democracy Shapes Health Outcomes˗ - Federico Maggio; Dominic Rohner; Alessandro Saia (CESifo GmbH, 2024)
The variation in life-expectancy and health outcomes across countries and cohorts is striking. While medical progress and climatic factors have received much attention, there is only relatively little we know about the health impact of exposure to institutional environments over the life cycle. The present study investigates how exogenous variation in cumulative childhood exposure to democracy shapes adult health outcomes. It is found that growing up in bad regimes lastingly damages lifetime health, even when living as adult in a more favorable institutional environment. The key channels of transmission include income effects, and a series of policy recommendations are formulated.
Keywords: D74; N92; Z10; 330; democracy; health; early childhood exposure